2019
DOI: 10.1002/eap.1913
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for ocean connectivity and hydroclimate in fish recruitment fluctuations within transboundary metapopulations

Abstract: Marine resources stewardships are progressively becoming more receptive to an effective incorporation of both ecosystem and environmental complexities into the analytical frameworks of fisheries assessment. Understanding and predicting marine fish production for spatially and demographically complex populations in changing environmental conditions is however still a difficult task. Indeed, fisheries assessment is mostly based on deterministic models that lack realistic parameterizations of the intricate biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…A similar result was observed by Hidalgo et al. (2019) who found that retention influenced recruitment in European Hake populations characterised by high drift to and from other areas in the northwest Mediterranean.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…A similar result was observed by Hidalgo et al. (2019) who found that retention influenced recruitment in European Hake populations characterised by high drift to and from other areas in the northwest Mediterranean.…”
Section: Discussionsupporting
confidence: 88%
“…While the effect of transport on recruitment has previously been explored using coupled biological‐oceanographic models (e.g. Daewel et al., 2015;Hinrichsen et al., 2016), direct inclusion of ELS dispersal model output in stock–recruitment models is less common (but see Hidalgo et al., 2019). Some studies have used proxies for larval transport such as wind speed (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations